2010
DOI: 10.1161/hypertensionaha.110.156547
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Determinants of Myocardial B-Type Natriuretic Peptide Release

Abstract: Abstract-Although B-type natriuretic peptide (BNP) is widely used as a biomarker for heart failure, the in vivo mechanical stimulus for its cardiac release remains poorly defined. We aimed to characterize the hemodynamic determinants of the transcardiac BNP gradient as a measure of myocardial BNP release by performing a detailed hemodynamic assessment in subjects with a broad spectrum of systolic and diastolic left ventricular dysfunction. Forty-two subjects underwent a detailed transthoracic echocardiographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(33 citation statements)
references
References 33 publications
2
28
0
1
Order By: Relevance
“…Therefore, we applied BNP, not NT-proBNP, as a prognostic surrogate marker in this study. It is reported that left ventricular end-systolic wall stress is the key mechanical stimulus for cardiac BNP release [34]. Our data demonstrated that the change in BNP levels is correlated to the changes in AI and cPP.…”
Section: Discussionsupporting
confidence: 67%
“…Therefore, we applied BNP, not NT-proBNP, as a prognostic surrogate marker in this study. It is reported that left ventricular end-systolic wall stress is the key mechanical stimulus for cardiac BNP release [34]. Our data demonstrated that the change in BNP levels is correlated to the changes in AI and cPP.…”
Section: Discussionsupporting
confidence: 67%
“…33 However, tools for assessing congestion in AHF, including biomarkers and noninvasive devices, remain limited. 34,35 Implantable hemodynamic monitors, if approved, should provide important new understanding of the relationship among filling pressures, renal function, and outcomes in AHF. 36 These tools may also help to explain a negative impact of improved renal function [29][30][31] by identifying patients in whom WRF occurred before admission.…”
Section: Discussionmentioning
confidence: 99%
“…The likely explanation is that exercise causes increase in venous return leading to atrial stretch causing increase release of natriuretic peptides. Other determinant factors of pro-BNP include age, left ventricular hypertrophy, ventricular dysfunction (i.e., decreased ejection fraction and/or increased left ventricular end diastolic pressure) and subclinical myocardial injury and ischemia 21,[27][28][29] .…”
Section: Discussionmentioning
confidence: 99%